206 Unexpected Therapeutic Responses in Sexual Function in Women Prescribed Flibanserin for Hypoactive Sexual Desire Disorder. Issue 1 (1st April 2022) - Goldstein, I; Patel, S; Donatucci, S; Faragasso, A; Tojino, S
ABSTRACT: Introduction: Flibanserin is a multifunctional serotonin agonist and antagonist for the treatment of acquired, generalized hypoactive sexual desire disorder (HSDD). Flibanserin is approved for use in premenopausal women in the US and in both premenopausal and postmenopausal women ≤60 years old in Canada. A post-hoc analysis of Female Sexual Function Index (FSFI) scores from pivotal trials in premenopausal women with HSDD indicated significant improvements in total and individual domain scores after treatment initiation with flibanserin compared to placebo. Objective: The purpose of this case report study is to examine the postmarketing database to determine whether improvements in other aspects of sexual function have also been reported by women who were prescribed flibanserin in real world use outside of clinical trials. Methods: A search was performed in the global safety database to identify postmarketing case reports from August 2015 to March 2021. "Therapeutic response unexpected" was the Medical Dictionary for Regulatory Affairs (MedDRA 23.1) preferred term used in this search strategy. Study results include only case reports with narratives containing verbatim terms relevant to the domains on the FSFI (arousal, lubrication, orgasm, pain, satisfaction), excluding desire as this is an expected response. Results: Thirty-two postmarketing case reports, including 13 patient testimonials of "therapeutic response unexpected", were identified during this period. Of these 32 case reports, 12 (38%) contained terms related to unexpected improvements in sexual function. Among the 12 reports of improved sexual function, 10 (83%) included terms related to increases in frequency, intensity, or duration of orgasms, one of which also mentioned improvement in arousal. The remaining 2 cases included 1 report of improvement in lubrication and 1 report of improvement in pain. Conclusions: These postmarketing case reports are consistent with the post-hoc analyses of the data from the flibanserin clinical trials and provide further support that flibanserin therapy can lead to improvement in multiple aspects of sexual function in addition to sexual desire. Disclosure: Yes, this is sponsored by industry/sponsor: Sprout Pharmaceuticals Clarification: Industry initiated, executed and funded study Any of the authors act as a consultant, employee or shareholder of an industry for: Sprout Pharmaceuticals